The study of Salvinia molesta growth with the variation of light intensity - Siti Hardiastuti (Jurnal Agrivet, 2012)
The objectives of research were to identify the effects of light intensity to the growth and anatomy of Salvinia molesta. Research was conducted in Nanggulan Maguwoharjo, Depok, Sleman with altitude of 113 m asl. The materials were Salvinia molesta, vertisol soil, and urea. The investigation parameters were: the time of initial leaf emerge, number of leaves, diameter of leaf, the length of internodes, length of root, dry weight of plant, percentage of coverage, ratio of root/canopy, rate of relative growth, number of stomata, number of trichoma, the thickness of cuticle and leaf chlorophyll. The results showed that the growth of Salvinia molesta was affected by light intensity. Highest dry weight was gained with light intensity of 100%. The rate of initial growth increased at the age of 14 up to 28 days, but number of stomata and trachoma. Highest chlorophyll content was on the treatment of 25% light intensity